Screening of differentially methylated genes in skeletal fluorosis of rats with different types and involvement of aberrant methylation of Cthrc1 - Ding, Hongwei; Yin, Congyu; Yang, Menglan; Zhou, Ruiqi; Wang, Xilan; Pan, Xueli (Environmental pollution (1987), 2023)
Fluoride is a widespread pollutant in the environment. There is a high risk of developing skeletal fluorosis from excessive fluoride exposure. Skeletal fluorosis has different phenotypes (including osteosclerotic, osteoporotic and osteomalacic) under the same fluoride exposure and depends on dietary nutrition. However, the existing mechanistic hypothesis of skeletal fluorosis cannot well explain the condition's different pathological manifestations and their logical relation with nutritional factors. Recent studies have shown that DNA methylation is involved in the occurrence and development of skeletal fluorosis. DNA methylation is dynamic throughout life and may be affected by nutrition and environmental factors. We speculated that fluoride exposure leads to the abnormal methylation of genes related to bone homeostasis under different nutritional statuses, resulting in different skeletal fluorosis phenotypes. The mRNA-Seq and target bisulfite sequencing (TBS) result showed differentially methylated genes in rats with different skeletal fluorosis types. The role of the differentially methylated gene Cthrc1 in the formation of different skeletal fluorosis types was explored in vivo and in vitro. Under normal nutritional conditions, fluoride exposure led to hypomethylation and high expression of Cthrc1 in osteoblasts through TET2 demethylase, which promoted osteoblast differentiation by activating Wnt3a/β-catenin signalling pathway, and participated in the occurrence of osteosclerotic skeletal fluorosis. Meanwhile, the high CTHRC1 protein expression also inhibited osteoclast differentiation. Under poor dietary conditions, fluoride exposure led to hypermethylation and low expression of Cthrc1 in osteoblasts through DNMT1 methyltransferase, and increased the RANKL/OPG ratio, which promoted the osteoclast differentiation and participated in the occurrence of osteoporotic/osteomalacic skeletal fluorosis. Our study expands the understanding of the role of DNA methylation in regulating the formation of different skeletal fluorosis types and provides insights into new prevention and treatment strategies for patients with skeletal fluorosis. [Display omitted] •Cthrc1 was differentially methylated in different skeletal fluorosis types.•Fluoride caused Cthrc1 hypomethylation and promoted osteogenesis with normal nutrition.•Fluoride caused Cthrc1 hypermethylation and promoted osteolysis with poor nutrition.•CTHRC1 inhibited osteoclast differentiation regardless of normal or low nutrition.